Perceived advantages and disadvantages of organized sport and exercise activities in a Greek refugee camp: A qualitative approach - Florian Knappe; Nadia Filippou; Zeinab Ghiami; Marianne Meier; Luce Pieters; Nicola Quadri; Karim Ramadan; Iohannes D. Morres; Antonis Hatzigeorgiadis; Markus Gerber (Bern Open Publishing, 2023)
Human made conflicts and natural disasters led to a doubling of forced displacement in the past 10 years (United Nations High Commissioner for Refugees, 2022). Forcibly displaced people are generally challenged with severe mental and physical strains before, during and after their flight. Whereas forcibly displaced people show high levels of resilience (Dangmann et al., 2021), their risk of mental health struggles is markedly increased (Mesa-Vieira et al., 2022). The objective of this study was to explore the perception of regular participation in a co-designed and tailored sport and exercise intervention among adults living in a Greek refugee camp. The methodological approach relied on ethnography including informal discussions and participative observations. Data was collected and documented daily in a research diary over a period of eight months. Additionally, debrief meetings with the coaches (4 women and 4 men) were held regularly. These insights built the basis for a critical understanding and interpretation of 13 focus group discussions (n = 49, 19 women) and 38 self-recorded testimonies (17 women). Focus group discussions were conducted after a 10-week physical activity intervention period. The same participants were asked, after a 10-week follow-up, to provide a self-recorded testimony. Overall, 58 (55.8%) of the participants took part in the physical activities on a regular basis. Regular participation benefitted domains of psychological well-being, social cohesion, personal competencies, change in behavior and physiological health. However, some of the same domains were likewise negatively affected for certain participants, namely social cohesion and physiological health. The results indicate that organized sport and exercise activities have the potential to positively impact the living conditions of adults living in a Greek refugee camp. However, participation is not imperatively beneficial and only a specific target population can be addressed. References Dangmann, C., Solberg, Ø., Myhrene Steffenak, A. K., Høye, S., & Andersen, P. N. (2021). Syrian refugee youth resettled in Norway: Mechanisms of resilience influencing health-related quality of life and mental distress. Frontiers in Public Health, 9, Article 711451. https://doi.org/10.3389/fpubh.2021.711451 Mesa-Vieira, C., Haas, A. D., Buitrago-Garcia, D., Roa-Diaz, Z. M., Minder, B., Gamba, M., Salvador, D., Gomez, D., Lewis, M., Gonzalez-Jaramillo, W. C., Pahud de Mortanges, A., Buttia, C., Muka, T., Trujillo, N., & Franco, O. H. (2022). Mental health of migrants with pre-migration exposure to armed conflict: A systematic review and meta-analysis. The Lancet Public Health, 7(5), e469-e481. https://doi:10.1016/S2468-2667(22)00061-5 United Nations High Commissioner for Refugees. (2022). Global Trends. Forced Displacement in 2021. Retrieved from https://www.unhcr.org/publications/brochures/62a9d1494/global-trends-report-2021.html